Pengaruh Pemakaian Bahan Organik terhadap Produksi Tanaman Melon (Cucumis melo. L) - Risnawati Risnawati (AGRIUM: Jurnal Ilmu Pertanian, 2014)
This study aims to determine the effect of the use of organic (manure and compost) on the production of melon plants (Cucumis melo.L). The experimental design used was a non-factorial CRD with four types of treatment are: P0 = Without manure (control), P1 = manure cow manure, farmyard manure P2 = P3 = chicken manure and compost. Parameters measured were started flowering time, harvest time, fruit diameter, fruit weight and fruit diameter. The results showed that the treatment P0 yellow leaves, large stems, time starts to flower 23 days, the time of harvest life of 89.8 days, 0.15 kg fruit weight, fruit diameter of 9.2 cm and 1.35 cm thick flesh. P1 looks at the treatment of green leaves, large stems, time starts to flower 21 days, the time of harvest life of 78.8 days, 1.09 kg fruit weight, fruit diameter of 19.42 cm and 2.07 cm thick flesh. In the treatment of P2 looks green leaves, large stems, flowering age of 20 days, 76.8 days of harvest age, weight 1.18 kg fruit, fruit diameter and 20.49 cm by 2.71 cm thick flesh. At P3 treatment looks yellow leaves, small stems, flowering age of 22 days, 85.8 days of harvest age, weight 0.42 kg fruit, fruit diameter and 14.05 cm 1.98 cm thick flesh. Manure chicken manure very significant effect on the production of melon plants.  Keywords: Cucumis melo. L, organic matter (manure and compost), production